2008
DOI: 10.1007/s12328-008-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma arising from gastric duplication: a case report with literature review

Abstract: Gastric duplication is a rare congenital malformation. We report the case of a 50-year-old man with adenocarcinoma derived from gastric duplication. He was referred to our institute because of persistent vomiting due to pyloric stenosis. Abdominal computed tomography revealed two cystic lesions: a 2-cm mass located along the greater curvature of the upper gastric corpus and a 3-cm mass adjacent to the bulbus. Under the diagnosis of gastric duplication cysts, the oral cyst was removed with the gastric wall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Shibahara et al (2009) reported a case of bronchogenic cyst of the stomach located at the opposite side wall to the gastric adenocarcinoma, and attributed the adenocarcinoma to the chronic inflammation from the bronchogenic cyst to the gastric mucosa. Worth mentioning, because of persistent exposure to carcinogenic substances, alimentary duplication cyst should be recognized as a lesion at risk for malignant transformation in patients aged more than 50 years (Fukumoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Shibahara et al (2009) reported a case of bronchogenic cyst of the stomach located at the opposite side wall to the gastric adenocarcinoma, and attributed the adenocarcinoma to the chronic inflammation from the bronchogenic cyst to the gastric mucosa. Worth mentioning, because of persistent exposure to carcinogenic substances, alimentary duplication cyst should be recognized as a lesion at risk for malignant transformation in patients aged more than 50 years (Fukumoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is performed not only for the consideration of symptomatic relief and the prevention of potential complications caused by GDCs such as obstruction, torsion, perforation, bleeding, but also for the risk of malignant transformation in GDCs[3,7]. We performed a review of the English papers about GDCs in the past 17 years on PubMed and found that the majority of those cases had a good prognosis with complete symptomatic relief after surgical resection while only a few cases with malignant transformation developed recurrence or metastasis[11,12,14,23-25].…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma arising from GDCs lined by PCCE was not always found in reports, but there are still debates about GDC malignant transformations. [32][33][34][35][36] The author related it to the lasting action of chronic inflammation in duplication cysts. Fuku- moto 33 insists that it is a red alert for those who are identified with GDCs and older than 50, because of continuous exposure to carcinogenic substances.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] The author related it to the lasting action of chronic inflammation in duplication cysts. Fuku- moto 33 insists that it is a red alert for those who are identified with GDCs and older than 50, because of continuous exposure to carcinogenic substances. In the case we presented, the fluid drained from the cyst contained extremely high levels of CEA, CA19-9, and CA-125, which questioned the meaning of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%